Terrestrial depositional systems deciphering complexities through multiple stratigraphic methods - Zeigler, Kate E.; Parker, William Gibson (Elsevier, 2017)
Terrestrial Depositional Systems: Deciphering Complexities through Multiple Stratigraphic Methods is the first collection of contributed articles that not only introduces young geoscientists to biostratigraphy, chemostratigraphy, magnetostratigraphy, and lithostratigraphy, but also provides seasoned practitioners with a standard reference that showcases the topic’s most recent developments in research and application. When studying complex depositional systems, scientists often need to rely on more than one stratigraphic technique to truly understand the sequence of historical events. Through a blend of specific analytical techniques, experiments, sampling methods, and working examples, this book provides a practical reference for addressing a range of depositional system challenges. This multi-contributed reference combines reviews of stratigraphic methods with individual case studies, providing readers with a broad scope of techniques that will aid their work in the interpretation and understanding of complex depositional systems.--Provided by publisher.